Analisa Pengaruh Issue Overshooting Cell Terhadap Coverage dan Quality Jaringan 4G LTE Kelurahan Jati Baru Kota Padang - aulia, siska; Sonia Trirahmi; Dikky Chandra (UNIB Press, 2023)
The increase in service users causes network problems, such as poor signal quality, sudden signal loss, or no network at all, To improve network quality, improvements are made to service coverage. One of them is by adding eNodeB. With the addition of eNodeB, network maintenance must be carried out to ensure identification and improvement related to network coverage and performance. If maintenance is not performed, it can cause bad spots, one of which is cell overshooting. The purpose of this research is to analyse the effect of cell overshooting on 4G LTE network coverage and quality parameters. 4G network coverage parameters are: Reference Signal Received Power (RSRP) and 4G network quality parameters namely Signal to Interference Noise Ratio (SINR). From the drive test results obtained 80.77% of 546 samples on RSRP parameters ≥ -100 dBm and 32.78% of 546 samples on SINR parameters ≥ 3 dB. The low SINR parameter of the drive test results is caused by bad spot overshooting cell interference that occurs at site 4253364E and site MC425CC02E with sites around the bad spot area. From the analysis, it can be seen that bad spot overshooting cell affects network quality, while network coverage parameters do not. Where the RSRP parameters at the bad spot point are -87 dBm and -92 dBm and SINR parameters at the bad spot point are -1 dB and -3 dB.